The effect of a combination of kepok banana peel (musa acuminata balbisiana colla) and bay leaf (syzygium polyanthum) extracts on bleeding time in wistar rats (rattus norvegicus) - Sarinastiti, Deliza Dhiakhalda; Sudarsono, Tantri Analisawati; Dhanti, Kurnia Ritma; Wijayanti, Linda; Muniroh, Nur An-Nuha; Cahyaningrum, Winda Rahma; Putranti, Respatiningtyas Amadea Danfi; Hanifa, Noha (MEDIA ILMU KESEHATAN, 2024)
Background: The body injured potential for bleeding. Hemostatic drugs used to stop bleeding have many side effects. Kepok banana peels and bay leaves contain flavonoids and tannins which can stop bleeding.Objective: This study aims to determine the effect of a combination of kepok banana peel extract and bay leaves on bleeding time in Wistar rats. Methods: True experimental research type with post test only with control group design. 20 rats were divided into 5 groups, group K- was given aquadest, group K+ : epinephrine 1mg/1ml, group F1: kepok banana peel extract and bay leaves 25%:75%, group F2 was given extract 50:50%, and group F3 was given 75%:25% extract. Results: One Way ANOVA test obtained a value of p=0,002 showing that there was a significant difference in the time to stop bleeding for each treatment group, followed by the Post Hoc Games Howell test.Conclusion: The F3 group with a combination of 75% kepok banana peel extract and 25% bay leaf extract was the most effective group in accelerating bleeding time in Wistar rats